Kajian Aplikasi Mikroorganisme Lokal Bonggol Pisang dan Mikoriza Pada Media Tanam Terhadap Karakter Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jacq.) - Sylvia Madusari (Politeknik Kelapa Sawit Citra Widya Edukasi, 2018)
Indigenous Microorganisms (IMO) of the banana corm and mycorrhiza, each has a potential to increase the availability and the absorption of the nutrient by plant and also increasing the plant growth, as pre-nursery of palm oil. The aim of this study is to analyze the character of the oil palm (Elaeis guineensis Jacq.) seedling growth by applying the combination of the mycorrhiza and the liquid of banana corm (IMO) organic fertilizer to the plant media which contained subsoil and cow dung. The study was performed in four of treatments including the control and were arranged in completely randomized design (CRD). The treatment dose of liquid organic fertilizer and mycorrhiza applied at a single dose. The whole treatments were P0 = 100% subsoil; P1 = subsoil and cow dung (1:1); P2 = subsoil and cow dung (1:1) + dose 100% inorganic fertilizers; P3 = subsoil and cow dung (1:1) + organic fertilizer 40 ml/polybag + Mycorrhiza 10 g/polybag. The chemical properties of the media was analyzed prior to the trial and the result showed mean amount of 2.81% C, 0.27% N, 1.12 mg/Kg P, 6.77 cmol/Kg K, 2.03 cmol/Kg Mg, and 18.24 cmol/Kg CEC. Plant height, plant diameter, leaf number and leaf area was the highest in plant treated with inorganic fertilizer. The leaf greeness and the density of stomata in plant treated with liquid organic fertilizer and mycorrhiza was slightly higher than control but lower than inorganic fertilizer treatment. Futher study are needed to determine optimal rates of applying combination of liquid organic fertilizer and mycorrhiza for proper growth of oil palm seedlings.